Políticas de Preservação Digital em Bibliotecas Universitárias - Nuno Emanuel Paiva de Andrade (2024)
The aim of this dissertation is to develop a digital preservation policy that serves as a basic model for documentation and information services in academic institutions, allowing these institutions to formalise in a transparent way the policies and practices that underlie the life cycle of information, with a focus on the long-term digital preservation of the information types they have selected. The following is an example of how this digital preservation policy can be implemented, using the Documentation and Information Service (SDI) of the Faculty of Engineering of the University of Porto (FEUP) as a case study. The methodology used consisted of carrying out a literature review between 2013 and 2023 in various databases, in which documents of interest to the literature review were identified after reading the title and abstract. The literature review was complemented by an exploratory search in the Open Repository of the University of Porto and in Internet search engines, where it was possible to identify additional documents of interest to this dissertation. Following the literature review, data collection began by interviewing the Director of the SDI, the Coordinator of the Discovery Support Team and the Coordinator of the Information Representation Team of the Library Unit (UB) of FEUP's SDI, with the aim of complementing a functional analysis of the UB and identifying the types of documents chosen for long-term digital preservation. This was followed by a comparative case study which consisted of a comparative analysis of the content of various digital preservation policies existing in academic institutions, identified in the literature review and exploratory research, with the aim of identifying common and divergent points between them. Based on the conceptual and technical knowledge presented in the literature review, the analysis of the data collected in the functional analysis of the UB of FEUP's SDI and the comparative analysis of existing digital preservation policies at other university institutions, a digital preservation policy applicable to university documentation and information services was devised with the respective implementation guide.